Controllable membrane electrode carbon carrier, catalyst and preparation method thereof
By preparing a controllable carbon support with a multi-stage pore structure and loading precious metals, the problem of limitation of the existing membrane electrode carbon support structure is solved, and the performance of the catalyst and the cyclic stability of the membrane electrode are significantly improved.
Patent Information
- Application Number
- CN202411526056.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The single pore size and fixed structure of the existing membrane electrode carbon support limit the multi-stage loading of precious metal particles and the efficient hydrophilic mass transfer effect, resulting in low catalyst reaction rate and poor durability, limiting the performance and large-scale application of membrane electrodes.
Controllable carbon support is prepared by hydrothermal reaction using aluminum nitrate hexahydrate and 1,3,5-benzenetrialic acid, and is treated by metal salt activation and sodium borohydride reduction to form a carbon support with a multi-stage pore structure and a high specific surface area. , used to prepare catalysts for supporting precious metals.
The dual adjustment of the size and pore size of the carbon support is achieved, the hydrophilic gas-repellent efficiency of the catalyst and the loading capacity of the precious metal particles are improved, and the circulation stability and mass transfer efficiency of the membrane electrode are significantly improved.
Smart Images

Figure CN119265603A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane electrode catalyst layers, and in particular relates to a controllable membrane electrode carbon carrier, a catalyst and a preparation method thereof. Background Art
[0002] Driven by the "dual carbon" goals, proton exchange membrane electrolysis technology has attracted widespread attention for its ability to convert unstable energy into green hydrogen. Its efficient and clean energy storage method provides an insightful solution for sustainable development.
[0003] As the core component in the field of water electrolysis and fuel cells, membrane electrode plays a vital role. Its components mainly include proton exchange membrane, catalyst layer and diffusion layer. The coordination between different components jointly affects the performance of membrane electrode.
[0004] The catalyst layer is the area where the electrochemical reaction occurs in the membrane electrode. Its efficiency and stability have a decisive influence on the overall electrochemical performance of the membrane electrode. At present, the catalysts commonly used in the catalyst layer are mainly platinum-based materials. The high consumption of precious metals limits the cost-effectiveness of the membrane electrode and even the entire water electrolysis and fuel cell system. Reducing the use of platinum while ensuring that performance is not affected has become the key to reducing the cost of water electrolysis systems and fuel cells. Therefore, reducing the catalyst loading, carefully designing the catalyst layer structure and optimizing its configuration to improve the overall performance have become the key work directions of membrane electrode researchers.
[0005] Among them, carbon materials have become the most commonly used carrier materials in water electrolysis and fuel cells due to their porosity, large specific surface area, and adjustable surface chemical properties. However, the types and contents of oxygen-containing functional groups on the surface of carbon carriers currently on the market are small, resulting in poor hydrophilic and gas-repellent effects; in addition, the fixed porosity and pore size make their specific surface area small, and have a large charge transfer resistance, which greatly reduces their mass transfer rate and precious metal particle loading capacity; thus, the performance of the membrane electrode is reduced, which seriously limits its large-scale application. However, a carbon carrier of the present invention has a regular hexagonal stereo structure, which has a larger attachment area and higher stability than other shapes; more importantly Yes, it can meet the requirements of high hydrophilicity and high mass transfer efficiency in membrane electrode work. Therefore, this kind of carbon carrier with regular hexagonal stereostructure and adjustable inside and outside is of great significance in the application of water electrolysis membrane electrode and fuel cell membrane electrode.
[0006] Traditional membrane electrodes in the field of water electrolysis and fuel cells cannot meet the requirements of multi-level loading of precious metal particles and efficient hydrophilic mass transfer due to the single pore size of the carbon carrier, resulting in low catalyst reaction rate; in addition, the fixed size and structure of the carbon carrier will also cause uneven stress distribution during the reaction, resulting in poor durability. Therefore, it is very necessary to develop a membrane electrode carbon carrier and catalyst with dual internal and external pore size adjustment. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a controllable membrane electrode carbon carrier and catalyst. The carbon carrier prepared by the present invention is loaded with precious metals to prepare catalysts and membrane electrodes, which show excellent cycle stability.
[0008] In order to achieve the above object, the first aspect of the present invention discloses a method for preparing a controllable membrane electrode carbon carrier, the preparation method comprising the following steps:
[0009] S1: dissolving aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 1,3,5-benzenetricarboxylic acid in a mixed solution of NN-dimethylformamide (DMF) and deionized water (DI), taking out after the hydrothermal reaction, washing and drying to obtain the prepared material;
[0010] S2: fully mixing the prepared material with the metal salt, treating at high temperature under an inert atmosphere, and after the reaction is completed, uniformly mixing the reaction product with the acid solution, and then washing and drying to obtain the controllable membrane electrode carbon support;
[0011] Wherein, in S1, the molar ratio of the aluminum nitrate hexahydrate to 1,3,5-benzenetricarboxylic acid is 1:1-3:1, and the volume proportion of the NN-dimethylformamide in the mixed solution is 10%-90%;
[0012] In S2, the metal salt includes potassium salt, zinc salt and magnesium salt; the mass ratio of the preparation material to the metal salt is 1:1-3:1; the high temperature treatment condition is 700-900°C;
[0013] In S2, the acid solution is a hydrochloric acid aqueous solution or a sulfuric acid aqueous solution, and the molar concentration of hydrogen ions in the acid solution is 6 to 12 mol / L.
[0014] Preferably, in S1, the hydrothermal reaction temperature is 150-170° C.; and the hydrothermal reaction time is 18-30 h.
[0015] The potassium salt is selected from one or more combinations of potassium hydroxide (KOH), potassium carbonate (K2CO3), potassium ferrate (K2FeO4), potassium sulfate (K2SO4), potassium bicarbonate (KHCO3), potassium citrate (C6H5O7K3·H2O), potassium acetate (C2H3KO2) or potassium oxalate (K2C2O4·H2O);
[0016] The zinc salt is selected from a combination of one or more of zinc sulfate, zinc carbonate or basic zinc carbonate;
[0017] The magnesium salt is selected from one or more combinations of magnesium sulfate, magnesium nitrate or basic magnesium carbonate.
[0018] Preferably, in S2, the reaction product and the acid solution are stirred and mixed at 50-70° C. for 12-36 hours.
[0019] In S2, the drying condition is: placing at 60-80°C for 24-48 hours.
[0020] The second aspect of the present invention discloses a controllable membrane electrode carbon carrier, which is prepared by the above preparation method.
[0021] The third aspect of the present invention discloses a catalyst prepared from the above controllable membrane electrode carbon carrier.
[0022] The method for preparing the catalyst comprises the following steps:
[0023] The controllable membrane electrode carbon support and the noble metal salt are stirred and uniformly mixed in an aqueous solution, and then a sodium borohydride solution is added for stirring and reduction treatment, and after the reaction is completed, the catalyst is washed and dried to obtain the catalyst;
[0024] Preferably, the noble metal salt is selected from chloroplatinic acid, platinum tetrachloride, potassium chloroplatinate, rhodium trichloride, iridium trichloride, ruthenium dioxide or ruthenium trioxide;
[0025] Preferably, the mass ratio of the controllable membrane electrode carbon support to the noble metal salt is 20:1-10:1; the ratio of the mass of sodium borohydride contained in the sodium borohydride solution to the mass of the noble metal salt is 5:1-15:1;
[0026] Preferably, the sodium borohydride concentration is 30 to 60 mol / L;
[0027] Preferably, the reduction treatment is carried out under stirring at 300-500 rpm for at least 24 hours;
[0028] Preferably, the drying condition is 60-80° C. for 24-48 hours.
[0029] The fourth aspect of the present invention discloses a membrane electrode, which comprises the above-mentioned catalyst.
[0030] The fifth aspect of the present invention discloses the application of the above-mentioned controllable membrane electrode carbon carrier, or the above-mentioned catalyst, or the above-mentioned membrane electrode in the field of water electrolysis membrane electrode and fuel cell membrane electrode.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The controllable membrane electrode carbon carrier and catalyst preparation method of the present invention selects a new carbon material precursor and a novel activation treatment method based on the conventional potassium salt activation pore formation. It is unexpectedly found that the size of the carbon material can be effectively controlled by this modification method, and more importantly, the size of the internal pore size of the carbon material can be controlled, thereby obtaining a size-controlled multi-level pore structure carbon carrier, and different types of catalysts. Further, through analysis, it is known that the use of different metal salts for activation can introduce different amounts of oxygen-containing functional groups into the carbon carrier, thereby improving its hydrophilic and gas-repellent efficiency; at different high-temperature treatment temperatures, the carbon carrier has a high specific surface area, a hierarchical pore structure and a low charge transfer resistance, indicating that it can greatly improve its mass transfer efficiency, and at the same time has an excellent precious metal particle loading capacity; in addition, the above-mentioned carbon carrier is loaded with precious metals to prepare catalysts and membrane electrodes, showing excellent cycle stability. In particular, the carbon carrier and catalyst of the present invention can be applied to the fields of water electrolysis membrane electrodes and fuel cell membrane electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 , Schematic diagram of the carbon carrier preparation process;
[0034] Figure 2 , Example 1 (a), Example 2 (b), Example 3 (c), Example 4 (d) and Example 5 (e) carbon support SEM;
[0035] Figure 3 , Example 1 Carbon support BET (N2 adsorption / desorption isotherm and pore size distribution curve);
[0036] Figure 4 , Example 2 Carbon support BET (N2 adsorption / desorption isotherm and pore size distribution curve);
[0037] Figure 5 , Example 3 Carbon support BET (N2 adsorption / desorption isotherm and pore size distribution curve);
[0038] Figure 6 , Example 4 Carbon support BET (N2 adsorption / desorption isotherm and pore size distribution curve);
[0039] Figure 7 , Example 5 Carbon support BET (N2 adsorption / desorption isotherm and pore size distribution curve). DETAILED DESCRIPTION
[0040] The technical scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the scope of the embodiments. The process parameters not specified in the embodiments of the present application can be carried out according to conventional methods, and the raw materials used can be obtained through commercial channels.
[0041] Example 1
[0042] Step 1): 10 mmol of aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 10 mmol of 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solution of 10 mL of N-N-dimethylformamide (DMF) and 50 mL of deionized water (DI), transferred into a 70 mL reactor, placed in a water heating box and reacted at 150°C for 18 hours to obtain the prepared material.
[0043] Step 2): The prepared material and potassium citrate are fully mixed in a mass ratio of 1:1, placed in a tubular furnace, and treated at high temperature under a N2 atmosphere (700°C for 2h, a heating rate of 5°C / min). After the reaction is completed, the product is evenly mixed with a 6 mol hydrochloric acid solution and placed at 50°C for 12 hours, and then placed at 60°C for 24 hours to dry to obtain the desired carbon support material.
[0044] Step 3): The carbon support material prepared above and chloroplatinate are stirred and evenly mixed in a mass ratio of 20:1 to prepare an aqueous solution, and then 30 mol of sodium borohydride solution is added in a mass ratio of 5:1 to chloroplatinate, and the mixture is subjected to a light-proof stirring reduction treatment at 300 rpm for 24 hours. After the reaction is completed, the mixture is filtered and dried at 60°C for 24 hours to obtain the desired catalyst.
[0045] Embodiment 2:
[0046] Step 1): 15 mmol of aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 10 mmol of 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solution of 50 mL of N-N-dimethylformamide (DMF) and 10 mL of deionized water (DI), transferred into a 75 mL reactor, placed in a water heating box and reacted at 155°C for 21 hours to obtain the prepared material.
[0047] Step 2): The prepared material is fully mixed with potassium acetate at a mass ratio of 1.5:1, placed in a tubular furnace, and treated at high temperature under a N2 atmosphere (750°C for 2h, a heating rate of 5°C / min). After the reaction is completed, the product is evenly mixed with a 6 mol hydrochloric acid solution and placed at 55°C for 18 hours, and then placed at 65°C for 30 hours to dry to obtain the desired carbon support material.
[0048] Step 3): The carbon support material prepared above and platinum tetrachloride salt are stirred and evenly mixed in a mass ratio of 18:1 to prepare an aqueous solution, and then 30 mol of sodium borohydride solution is added in a mass ratio of 8:1 to platinum tetrachloride salt, and the mixture is subjected to a light-proof stirring reduction treatment at 350 rpm for 24 hours. After the reaction is completed, the mixture is filtered and dried at 65°C for 30 hours to obtain the desired catalyst.
[0049] Embodiment 3:
[0050] Step 1): 20 mmol of aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 10 mmol of 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solution of 20 mL of N-N-dimethylformamide (DMF) and 40 mL of deionized water (DI), transferred into an 80 mL reactor, placed in a water heating box and reacted at 160°C for 24 h to obtain the prepared material.
[0051] Step 2): The prepared material is fully mixed with potassium oxalate in a mass ratio of 2:1, placed in a tubular furnace, and treated at high temperature under a N2 atmosphere (800°C for 2h, a heating rate of 5°C / min). After the reaction is completed, the product is evenly mixed with 6 mol sulfuric acid solution and placed at 60°C for 24 hours, and then placed at 70°C for 36 hours to dry to obtain the desired carbon support material.
[0052] Step 3): The carbon support material prepared above and potassium chloroplatinic acid salt are stirred and evenly mixed in a mass ratio of 15:1 to prepare an aqueous solution, and then 30 mol of sodium borohydride solution is added in a mass ratio of 10:1 to potassium chloroplatinic acid salt, and the mixture is subjected to a light-proof stirring reduction treatment at 400 rpm for 24 hours. After the reaction is completed, the mixture is filtered and dried at 70°C for 36 hours to obtain the desired catalyst.
[0053] Embodiment 4:
[0054] Step 1): 25 mmol of aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 10 mmol of 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solution of 40 mL of N-N-dimethylformamide (DMF) and 20 mL of deionized water (DI), transferred into an 85 mL reactor, placed in a water heating box and reacted at 165°C for 27 h to obtain the prepared material.
[0055] Step 2): The prepared material and basic zinc carbonate are fully mixed in a mass ratio of 2.5:1, placed in a tubular furnace, and treated at high temperature under a N2 atmosphere (850°C for 2h, a heating rate of 5°C / min). After the reaction is completed, the product is evenly mixed with a 6 mol sulfuric acid solution and placed at 65°C for 30 hours, and then placed at 75°C for 42 hours to dry to obtain the desired carbon support material.
[0056] Step 3): The prepared carbon support material and chloroplatinate are stirred and evenly mixed in a mass ratio of 12:1 to prepare an aqueous solution, and then 30 mol of sodium borohydride solution is added in a mass ratio of 12:1 to chloroplatinate, and the mixture is subjected to a light-proof stirring reduction treatment at 450 rpm for 24 hours. After the reaction is completed, the mixture is filtered and dried at 75°C for 42 hours to obtain the desired catalyst.
[0057] Embodiment 5:
[0058] Step 1): 30 mmol of aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 10 mmol of 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solution of 30 mL of N-N-dimethylformamide (DMF) and 30 mL of deionized water (DI), transferred into a 90 mL reaction kettle, placed in a water heating box and reacted at 170°C for 30 h to obtain the prepared material.
[0059] Step 2): The prepared material is fully mixed with basic magnesium carbonate in a mass ratio of 3:1, placed in a tubular furnace, and treated at high temperature under a N2 atmosphere (900°C for 2h, a heating rate of 5°C / min). After the reaction is completed, the product is evenly mixed with a 6 mol hydrochloric acid solution and placed at 70°C for 36 hours, and then placed at 80°C for 48 hours to dry to obtain the desired carbon support material.
[0060] Step 3): The prepared carbon support material and platinum tetrachloride salt are stirred and evenly mixed in a mass ratio of 10:1 to prepare an aqueous solution, and then 30 mol of sodium borohydride solution is added in a mass ratio of 15:1 to platinum tetrachloride salt, and the mixture is stirred and reduced at 500 rpm for 24 hours in a dark environment. After the reaction is completed, the mixture is filtered and dried at 80°C for 48 hours to obtain the desired catalyst.
[0061] Comparative Example 1:
[0062] The preparation method is the same as that of Example 1, except that the hydrothermal reaction conditions in step 1) are adjusted to react at 200° C. for 36 hours.
[0063] Comparative Example 2:
[0064] The preparation method is the same as that of Example 1, except that the high temperature treatment in step 2) is performed without metal salt activation.
[0065] Comparative Example 3:
[0066] The preparation method is the same as that of Example 1, except that in step 2), the ratio of the prepared material to the metal salt is adjusted to 5:1.
[0067] Comparative Example 4:
[0068] The preparation method is the same as that of Example 1, except that the high temperature treatment temperature in step 2) is adjusted to 1000°C.
[0069] Comparative Example 5:
[0070] The preparation method is the same as that of Example 1, except that in step 3), the mass ratio of sodium borohydride to the noble metal salt is adjusted to 2:1.
[0071] The specific surface area and pore size parameters of the carbon carriers in Examples 1-5 and Comparative Examples 1-5 were analyzed, as shown in Table 1 below.
[0072] Table 1
[0073]
[0074] From Table 1, Figure 3-7 It can be seen that the size of the precursor material prepared using aluminum nitrate hexahydrate and 1,3,5-benzenetricarboxylic acid is adjusted by adjusting the ratio of DMF and DI. Since the internal pore size characteristics of the carbon carrier prepared using precursors of different sizes are different, as the size of the precursor decreases, after activation by metal salts, its specific surface area shows a trend of gradually increasing.
[0075] From 295m in Example 1 2 g -1 , increased to 1502m in Example 5 2 g -1 . From the micropore ratio, mesopore ratio and average pore size in Table 1, it can be seen that the increase in its specific surface area is attributed to the increase in the proportion of micropores and mesopores during the activation process. Micropores and mesopores can provide more active area and adsorption sites for precious metal particles. In addition, it can be seen from Table 3 that the charge transfer resistance of catalysts prepared from different carbon carriers is different, which means that the adjustment of its external size and internal pore size can change the mass transfer efficiency of the carbon carrier. It can be seen that the external size of the carbon carrier can be controlled by controlling the ratio of DMF and DI in step 1), and the internal pore size of the carbon carrier can be regulated by activation pore formation, thereby realizing the preparation of controllable membrane electrode carbon carriers with dual internal and external pore size regulation.
[0076] Among them, the pore sizes mentioned in this application are divided into two types, namely, the stacked pores outside the carbon carrier and the interstitial pores inside the carrier. The stacked pores outside the carbon carrier are mainly caused by the pore structure caused by the accumulation of precursors of different sizes; the interstitial pores inside the carbon carrier are mainly caused by the activation of the inside of the carbon carrier by metal salts under high temperature conditions, thereby producing different pore sizes. This is caused by the combined effect of different sizes and different activation methods, just like the dual internal and external regulation strategy of pore size mentioned in the above content.
[0077] In addition, during the treatment of the carbon carrier, adjusting the high temperature treatment temperature will also cause changes in its specific surface area, micropore-mesopore ratio and average pore size. As shown in Example 4, at 1000°C, excessively high temperatures will cause the material structure to collapse and fail to maintain the original structure and pore size. The resulting carbon carrier has a smaller specific surface area and a larger charge transfer resistance, and the load capacity and mass transfer effect are reduced. In general, temperature can adjust the distribution of its multi-level pores and reduce the interfacial charge transfer resistance. The lower the charge transfer resistance, the better the interfacial electron transfer and interfacial mass transfer effects, and the more it can promote the effective transmission of water and gas, so as to achieve efficient mass transfer at the three-phase interface during the catalytic process.
[0078] Figure 2 The SEM images of the carbon carriers of Examples 1-5 show their excellent thermal stability. After activation at high temperature, they still maintain the original hexahedral structure without obvious structural collapse. In addition, the size gradient change of 5um-100nm further shows that the external size of the carbon carrier can be controlled. Further analysis combined with BET shows that while achieving external size regulation, the internal void structure is also gradient controlled.
[0079] The oxygen-containing functional group content of the carbon carriers in Examples 1-5 and Comparative Examples 1-5 was analyzed, as shown in Table 2.
[0080] Table 2
[0081]
[0082]
[0083] As can be seen from Table 2, the use of different metal salts for activation will have different effects on the surface functional groups of the product. Compared with samples activated without metal salts, the proportion of oxygen-containing functional groups increased after activation with metal salts, which mainly comes from the introduction of pyrolysis of metal salts during high temperature, which can change the surface environment of the carbon carrier. Specifically, this oxygen-containing functional group can increase the surface active sites of the carbon carrier, increase the hydrophilic and gas-repellent efficiency, and facilitate the loading of precious metal particles, thereby increasing the stability of the catalyst and membrane electrode during the cycle.
[0084] The performance of the catalysts and membrane electrodes prepared in Examples 1-5 and Comparative Examples 1-5 was analyzed, as shown in Table 3.
[0085] Table 3
[0086]
[0087]
[0088] As can be seen from Table 3, with the regulation of the external size and internal pore size of the carbon carrier, under the same load of precious metal particles, the catalysts prepared by the carbon carriers of Examples 1-5 have smaller charge transfer resistance and better overpotential, which shows that the large specific surface area and suitable pore structure can greatly improve the mass transfer efficiency and the loading capacity of precious metals, thereby preparing a catalyst with uniform precious metal particle loading. In addition, the carbon carrier prepared by this scheme to prepare the membrane electrode also shows excellent cycle stability. During the 500-hour stability test, the voltage only changes by 3.2-4.2μV / h, which is better than most current membrane electrodes. This further proves that the dual strategy of size control and pore size adjustment can effectively improve the performance of the catalyst, and is of great significance to the design of carbon carriers and the synthesis of catalysts in the current field of water electrolysis and fuel cells. In addition, adjusting the ratio of carbon carriers and precious metal salts during the catalyst preparation process will also cause changes in stability, so all such adjustments can be used to further optimize the stability of the membrane electrode during the experiment.
[0089] The present invention is not limited to the above-mentioned embodiments. Any changes in shape or structure shall fall within the protection scope of the present invention. The protection scope of the present invention is defined by the attached claims. Those skilled in the art may make various changes, modifications, substitutions, combinations and simplifications to these embodiments without departing from the principle and essence of the present invention. All of these shall be equivalent replacement methods and fall within the protection scope of the present invention.
Claims
1. A method for preparing a controllable membrane electrode carbon carrier, characterized in that: The preparation method comprises the following steps: S1: dissolving aluminum nitrate hexahydrate (Al(NO3)3·6H2O) and 1,3,5-benzenetricarboxylic acid in a mixed solution of NN-dimethylformamide (DMF) and deionized water (DI), taking out after the hydrothermal reaction, washing and drying to obtain the prepared material; S2: fully mixing the prepared material with the metal salt, treating at high temperature under an inert atmosphere, and after the reaction is completed, uniformly mixing the reaction product with the acid solution, and then washing and drying to obtain the controllable membrane electrode carbon support; Wherein, in S1, the molar ratio of the aluminum nitrate hexahydrate to 1,3,5-benzenetricarboxylic acid is 1:1-3:1, and the volume proportion of the NN-dimethylformamide in the mixed solution is 10%-90%; In S2, the metal salt includes potassium salt, zinc salt and magnesium salt; the mass ratio of the preparation material to the metal salt is 1:1-3:1; the high temperature treatment condition is 700-900°C; In S2, the acid solution is a hydrochloric acid aqueous solution or a sulfuric acid aqueous solution, and the molar concentration of hydrogen ions in the acid solution is 6 to 12 mol / L.
2. The preparation method according to claim 1, characterized in that: In S1, the hydrothermal reaction temperature is 150-170° C.; the hydrothermal reaction time is 18-30 h.
3. The preparation method according to claim 1, characterized in that: The potassium salt is selected from one or more combinations of potassium hydroxide (KOH), potassium carbonate (K2CO3), potassium ferrate (K2FeO4), potassium sulfate (K2SO4), potassium bicarbonate (KHCO3), potassium citrate (C6H5O7K3·H2O), potassium acetate (C2H3KO2) or potassium oxalate (K2C2O4·H2O); The zinc salt is selected from a combination of one or more of zinc sulfate, zinc carbonate or basic zinc carbonate; The magnesium salt is selected from one or more combinations of magnesium sulfate, magnesium nitrate or basic magnesium carbonate.
4. The preparation method according to claim 1, characterized in that: In S2, the reaction product and the acid solution are stirred and mixed at 50-70° C. for 12-36 hours.
5. The preparation method according to claim 4, characterized in that: In S2, the drying condition is: placing at 60-80°C for 24-48 hours.
6. A controllable membrane electrode carbon support, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. A catalyst, characterized in that It is made from the controllable membrane electrode carbon carrier described in claim 6.
8. The method for preparing the catalyst according to claim 7, characterized in that: The following steps are involved: The controllable membrane electrode carbon support of claim 6 and the noble metal salt are stirred and uniformly mixed in an aqueous solution, and then a sodium borohydride solution is added for stirring and reduction treatment, and after the reaction is completed, the catalyst is washed and dried to obtain the catalyst; Preferably, the noble metal salt is selected from chloroplatinic acid, platinum tetrachloride, potassium chloroplatinate, rhodium trichloride, iridium trichloride, ruthenium dioxide or ruthenium trioxide; Preferably, the mass ratio of the controllable membrane electrode carbon support to the noble metal salt is 20:1-10:1; the ratio of the mass of sodium borohydride contained in the sodium borohydride solution to the mass of the noble metal salt is 5:1-15:1; Preferably, the sodium borohydride concentration is 30 to 60 mol / L; Preferably, the reduction treatment is carried out under stirring at 300-500 rpm for at least 24 hours; Preferably, the drying condition is 60-80° C. for 24-48 hours.
9. A membrane electrode, characterized in that: It comprises the catalyst according to claim 7, or the catalyst prepared by the preparation method according to claim 8.
10. The controllable membrane electrode carbon carrier according to claim 6, or the catalyst according to claim 7, or the membrane electrode according to claim 9 is used in the fields of water electrolysis membrane electrode and fuel cell membrane electrode.
Citation Information
Patent Citations
Preparation method of non-noble metal direct methanol fuel cell anode catalyst
CN113299933A
Method for preparing carbon carrier and synthesizing Pt-Sn catalyst by calcining ZIF-8 molten salt
CN113745553A
Monatomic iron catalyst for electrocatalytic reduction of oxygen to water and preparation method and application of monatomic iron catalyst
CN114792815A
Anti-reverse nitrogen-carbon carrier catalyst for proton exchange membrane fuel cell and preparation method of anti-reverse nitrogen-carbon carrier catalyst
CN114824301A
Preparation method of bimetallic nitrogen-containing porous carbon catalyst
CN115020722A